EFEKTIVITAS PENERAPAN METODE CAMEL DALAM MENGUKUR KINERJA KEUANGAN PT BANK BNI SYARIAH CABANG MAKASSAR - Malinda Yusuf (Jurnal Ilmu Manajemen Profitability, 2019)
This study aims to get a clearer picture of the size of the bank's soundness, while the categories are healthy, fairly healthy, unhealthy, and unhealthy. This research was conducted at BNI bank. This grading system uses Quantitative methods, namely by quantifying the components included in each factor so that a certain value or number is obtained. Five-year ratios, namely 2013,2014, 2015, 2016 and 2017 BNi Islamic banks obtain CAR ratios (Capital Adequency Ratio) 16.54%, 19.29%, 15.46%, 14.92%, and 14.90% ≥ 8% categorized in the HEALTH group. Bank BNI Syariah productive assets (KAP) quality ratio in 2013, 2014, 2015, 2016, and 2017 amounted to 1.53%, 1.61%, 2.36%, 2.49%, and 2.63% ≤ 10 , 35% are categorized in the HEALTH group. Allowance for Removal of earning assets (PPAP) of Bank BNI Syariah in 2013, 2014, 2015, 2016, and 2017 amounted to 101.72%, 101.62%, 206.46%, 204.50%, and 208.64% ≤ 81 % is categorized in the HEALTH group. Bank BNI Syariah Cash Ratio in 2013, 2014, 2015, 2016, and 2017 amounted to 3.13%, 6.48%, 2.53%, 6.94%, and 4.29% ≥ 4.05% categorized in SEHAT group. Bank BNI Syariah's Loan to Deposit Ratio (LDR) ratio in 2013, 2014, 2015, 2016, and 2017 was 97.86%, 92.60%, 91.94%, 84.57%, and 81, respectively. 40% ≥ 94.75% is categorized in the HEALTH group.